Pengaruh Kepemilikan BPJS Kesehatan Terhadap Pemanfaatan Pelayanan Kesehatan di Kabupaten Pulau Morotai - Reni Ibrahim; Arifin M. Kahar (Jurnal Multidisiplin Madani, 2022)
Some researchers stated that the ownership of health insurance and the economic status affect health services utilization in an area. Therefore, this study aims to determine the effect of these two variables on the utilization of health services in Pulau Morotai. The research design is a cross-sectional study using the data from BPS-Statistics Indonesia through the 2021 National Socio-Economic Survey. Households and individuals were the target population and the unit of analysis. Moreover, the selected samples regarding inclusion and exclusion criteria were 419 individuals. The Binary Logistics Regression Model shows that the health insurance, namely the ownership of BPJS Kesehatan-Healthcare and Social Security Agency, is significant at an error rate of 0.05. Meanwhile, the analysis excluded the economic status because it had no relationship with health services utilization. The conclusion is that the BPJS Kesehatan ownership significantly affects health services utilization in Pulau Morotai.